To Determine the Resistance Patterns of Enterococcus Isolates Against Vancomycin, Linezolid, and Daptomycin: A Cross-Sectional Study - Dr. Shruti Sharma; Dr. Ashish Pareek; Dr. Kiran Meena (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The emergence of multidrug-resistant Enterococcus species, particularly vancomycin-resistant enterococci (VRE), poses a significant challenge in clinical settings. This study aimed to determine the resistance patterns of Enterococcus isolates against vancomycin, linezolid, and daptomycin. Methods: A total of 60 Enterococcus isolates were collected from clinical specimens (urine, blood, wound swabs) over six months. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method and minimum inhibitory concentration (MIC) determination for vancomycin (VAN), linezolid (LZD), and daptomycin (DAP). Results: Among the 60 isolates, Enterococcus faecalis (65%) was more prevalent than Enterococcus faecium (35%). Vancomycin resistance was observed in 18.3% (n=11) of isolates, with higher resistance in E. faecium (27.3%) than E. faecalis (12.8%). Linezolid resistance was detected in 6.7% (n=4), while daptomycin resistance was found in 5% (n=3). Multidrug resistance (MDR) was observed in 10% (n=6) of isolates. Conclusion: The study highlights increasing resistance to vancomycin and emerging resistance to linezolid and daptomycin among Enterococcus isolates. Continuous surveillance and strict antimicrobial stewardship are essential to curb resistance.